A Systematic Review of Fecal Microbiota Transplant for the Management of Pouchitis. Issue 2 (12th May 2020) - Kayal, Maia; Lambin, Thomas; Pinotti, Rachel; Dubinsky, Marla C; Grinspan, Ari
Abstract: Background: Manipulation of the pouch microbiota via fecal microbiota transplant (FMT) has been theorized to be a promising therapeutic approach for pouchitis. The goal of this systematic review was to summarize the available, high-quality data on the efficacy and safety of FMT for acute and chronic pouchitis. Methods: A systematic electronic literature search was conducted on Embase, MEDLINE, Scopus, and Cochrane CENTRAL. Randomized controlled trials and observational studies that assessed the efficacy and safety of FMT for the treatment of acute and/or chronic pouchitis in patients with ulcerative colitis who underwent total proctocolectomy with ileal pouch-anal anastomosis were included. Results: Four studies involving the use of FMT for chronic pouchitis were considered eligible for data extraction. No study involving the use of FMT for the management of acute pouchitis was identified. In 1 study, 3/5 (75%) patients achieved sustained clinical remission at 3 months. In the remaining 3 studies, 2/8, 1/11, and 1/5 patients achieved clinical response defined as a decrease in pouchitis disease activity index at least 3. Stool donor engraftment as determined by 16s rRNA gene sequencing occurred only in those patients with clinical response. Conclusions: The 4 studies that met inclusion criteria for this systematic review indicate FMT is safe in chronic pouchitis, however largely not efficacious. These data are limited by study heterogeneity. Additional studies are required to guide the use of FMT in patients with acute and chronic pouchitis. Lay Summary: A systematic review was conducted to assess the efficacy and safety of fecal microbiota transplant (FMT) for acute and chronic pouchitis. Four studies met the inclusion criteria. Results indicate FMT is safe in chronic pouchitis, however largely not efficacious.